Effects of Demographic Characteristics on Organizational Culture and Job Satisfaction among Faculties of Higher Education in Kathmandu, Nepal - Prajapati, Bikram; Khanal, Krishna; sharma, Rajiv (Journal of Business and Management, 2024)
Background: Organizations have been recognizing the value of culture because it helps attract, satisfy, and retain employees. The explicit nature of organizational culture pertains to visible artifacts and other observable elements within an organization. However, the implicit paradigms of organizational culture are often challenging to identify through mere observation. Organizational culture refers to the environment within a workplace created by its underlying values and practices, which in turn impacts employees’ job satisfaction.Objectives: This research investigates the impact of demographics characteristics on organisataional culture and job satisfaction.Methods: In this research, we analyzed the relationship between organizational culture and job satisfaction in a sample of 81 full-time faculty members using standard questionnaire from higher education institutions located in Kathmandu, Nepal using purposive sampling method.Results: It was observed that perceptions of different organizational cultures varied among different demographic variables. Factor analysis yielded four components of job satisfaction: accomplishment, supervision, empowerment, and growth. Correlational analysis demonstrated that the clan organizational culture exhibits a significant positive relationship with job satisfaction.Conclusion: Conducting this research on the impact of demographic characteristics on organizational culture and job satisfaction in higher education in Nepal will provide valuable insights to inform policies and practices that can enhance employee satisfaction and organizational effectiveness.